PENGUATAN GURU MIPA SMP SEBAGAI FASILITATOR PEMBELAJARAN BERBANTUAN SIMULASI PhET - Novitasari, Novitasari; Mayang Sari, Elisa; Riezky Pratiwi, Indah; Pebriano, Gagah (Jurnal Pengabdian Masyarakat Polmanbabel, 2024)
The fact that gadgets are no longer luxury items and every student certainly has them presents an opportunity for teachers to create meaningful learning. One way to do this is by conducting learning assisted by PhET Simulations. These simulations offer various concepts in mathematics, physics, biology, and chemistry to be taught in the form of simulations. The use of these simulations allows the role of the teacher as a learning facilitator to be effectively carried out theoretically. However, the use of simulations has not been carried out to assist teachers in teaching material. Strengthening needs to be done. The strengthening is carried out at SMP N 1 Pemali through providing focused reinforcement for Mathematics and Natural Sciences (IPA) teachers. The reinforcement implementation is equivalent to a 6-hour training with activities starting and ending with tests to see if there is any improvement in understanding related to the reinforcement provided. Information was obtained indicating a good improvement in understanding related to the use of PhET as a learning medium for teachers is 37,5 %. In addition, the reinforcement provided received a positive response. Reinforcement practice in using PhET simulations has a good impact on MIPA SMP’s teachers as facilitators in learning.